(untitled) (Journal of Pharmaceutical Negative Results, 2022)
This experiment conducted on rosemary plant (Rosmarinus officinalis L.), aimed to investigate the effect of gibberellic acid (GA3), salicylic acid (SA), and NPK fertilizer on growth and chemical constituents as well as determining the best concentration. After two weeks from planting the rooted cuttings in plastic pots were sprayed with the SA at three concentrations (0, 150 and 300 mg l-1), GA3 Sprayed with two concentrations (0, 400 mg l-1), and NPK sprayed as Nano NPK at concentrations (3 and 6 g l-1), the control plants were fertilized with regular fertilizer recommendation of NPK (200-N, 100-P, 50-K mg l-1). The results showed: The triple interaction among the three factors studied indicated that the plants which sprayed with 400 mg l-1 GA3, 300 mg l-1 SA, and 6 g l-1 nano NPK fertilizers gave the highest value number of branches 19.97 branch plant-1, volatile oil percent 1.626 %, and total chlorophyll content 32.70 mg g-1 f.w, whereas plant height increased to highest value at 400 mg l-1 GA3, 300 mg l-1 SA and 3 g l-1 nano NPK which reached to 38.30 cm, also production of volatile oil per plant increased at 400 mg l-1 GA3, 150 mg l-1 SA, and 6 g l-1 nano NPK fertilizers 0.947 ml plant-1. It appears that using those levels gave the best growth and development results on rosemary plant. Further research is needed to investigate whether the higher concentrations than used in this research will give the better parameters.